Thrombolytic Therapy for Right-Sided Mechanical Pulmonic and Tricuspid Valves: The Largest Survival Analysis to Date - Taherkhani, Maryam (Tex Heart Inst J, 2015)
Data regarding thrombolytic treatment of right-sided mechanical valve thrombosis are almost nonexistent, and all current guidelines arise from very small case series. We retrospectively studied the in-hospital and long-term outcome data of a larger series of patients who had received, from September 2005 through June 2012, thrombolytic therapy for right-sided mechanical pulmonary valve or tricuspid valve thrombosis. We identified 16 patients aged 8–67 years who had undergone thrombolytic therapy for definite thrombotic mechanical valve obstruction in the tricuspid or pulmonary valve position (8 in each position). All study patients except one had subtherapeutic international normalized ratios. The 8 patients with pulmonary mechanical valve thrombosis had a 100% response rate to thrombolytic therapy, and their in-hospital survival rate was also 100%. The 8 patients with tricuspid mechanical valve thrombosis had a 75% response rate to thrombolytic therapy, with an in-hospital survival rate of 87.5%. The one-year survival rate for mechanical valve thrombosis treated with thrombolytic therapy (whether pulmonary or tricuspid) was 87.5%. On the basis of our data, we recommend that thrombolytic therapy remain the first-line therapy for right-sided mechanical valve thrombosis in adults or children—including children with complex congenital heart disease and patients with mechanical pulmonary valve thrombosis. Surgery should be reserved for patients in whom this treatment fails.